Clinical epidemiological characterization of patients with pancreas cancer in a general surgery service - Oriol Valón Costa; Ana Lubín García; Danilo Romaguera Barroso; Lázaro Ibrahim Romero García (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The pancreas cancer constitutes one of the neoplasms with worse prognosis due to its late diagnosis.  Objective: To characterize patients with pancreas cancer according to clinical epidemiological variables and complementary exams.  Methods: An observational, descriptive and cross-sectional study of 70 patients with pancreas cancer was carried out, who were discharged from the General Surgery Service of Saturnino Lora Teaching Provincial Hospital in Santiago de Cuba during 2016-2020. The variables studied were: age, sex, risk factors, associated diseases, signs and symptoms and complementary exams.  Results: There was a prevalence of the male sex (54.2 %), the 51-70 age group, the ingestion of fatty foods and nicotine addiction and alcoholism as risk factors, the chronic alcoholism, diabetes mellitus and hypertension as more common associated diseases, as well as the general syndrome, jaundice and coluria among the most frequent signs and symptoms. On the other hand, according to the imaging studies, most of those affected were diagnosed by means of computerized axial tomography and abdominal echography (94.3 and 70.0 %, respectively).  Conclusions: The multiscan computerized axial tomography is the image technique of election recommended by the guides of international consent. The radiographic report is the key for later decisions making but there are circumstances of the patient that can affect them, such as age, risk factors, signs and symptoms and comorbidity, among others.